Gram-negative bacilli causing infections in an intensive care unit of a tertiary care hospital in Istanbul, Turkey - ÖZAYDIN, AYŞE NİLÜFER (J INFECTION DEVELOPING COUNTRIES, 2014)
Introduction: This study aimed to demonstrate the changing epidemiology of infecting microorganisms and their long-term resistance profiles and to describe the microbiological point of view in anti-infective management of intensive care unit (ICU) patients. Methodology: A total of 5,690 isolates of Gram-negative bacilli were included in this study. Antibiotic susceptibility was tested using the disk diffusion method and Vitek 2 system. Chi-square tests were used for hypothesis testing. Results: The most frequently isolated organisms were A. baumannii (37.3%), P. aeruginosa (30.3%), Enterobacter spp. (10.4%), E. coli (10.4%), and Klebsiella spp. (8.9%). A. baumannii was the most frequently isolated organism from the respiratory tract (43.4%); the susceptibility rates for imipenem and meropenem decreased to 7% and 6% (p < 0.0001), respectively. The percentage of multidrug-resistant (MDR) A. baumannii isolates continuously increased from 18.7% in 2004 to 69% in 2011 (p < 0.0001), whereas MDR P. aeruginosa isolates increased from 1.5% to 22% (p < 0.0001). Carbapenem-resistant Klebsiella isolates emerged in 2010 and increased to 20% in the next year. The rates of ESBL-producing Enterobacteriaceae in the ICU was very high in 2011 - 50% for E. coli and 80% for Klebsiella strains. Conclusion: The most common isolated Gram-negative bacillus in our study was A. baumannii and that the prevalence of MDR isolates has increased markedly over. Accordingly, the comparison of antibiotic resistance of other pathogens in 2004 and 2011 displayed an increasing trend. These data imply the urgent need for new and effective strategies in our hospital and in the region.
Keywords: Gram-negative bacilli; Antibiotic resistance; ICU; MDR; VENTILATOR-ASSOCIATED PNEUMONIA; ANTIMICROBIAL RESISTANCE; NOSOCOMIAL INFECTIONS; PSEUDOMONAS-AERUGINOSA; ACQUIRED INFECTIONS; SURVEILLANCE; SUSCEPTIBILITY; PROGRAM; PATHOGENS; PATTERNS